Republican Virtue and Court Virtue: Schillerʼs ’Fiesko’ and Goetheʼs ’Tasso’ - Salmerón Infante, Miguel (Revista de Filología Alemana, 2020)
This article compares two dramas by Schiller and Goethe, Die Verschwörung des Fiesko zu Genua (1783) and Torquato Tasso (1790), respectively. Fiesko introduces the struggle for a restoration of the Genoese Republic that would end with the Dorias’ despotic dictatorship. Tasso exposes the difficulties of a poet who develops his writing in a courtly environment. We mean, Schiller writes about republican virtues and so Goethe does about courtly virtues. Dramatic conflicts are outstanding in their typologies of the tragic. Schiller collides against despotism-freedom politics, and Goethe arises from the pressure that an external framework exerts on individuality. The unsolvable of both conflicts is a hint for contradictions dealing with republican and courtly virtues.